2000
DOI: 10.1128/jvi.74.13.5957-5967.2000
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Viral Dose and Transient Immunosuppression Enable Herpes Simplex Virus ICP0-Null Mutants To Establish Wild-Type Levels of Latency In Vivo

Abstract: The reduced efficiency with which herpes simplex virus type 1 (HSV-1) mutants establish latent infections in vivo has been a fundamental obstacle in efforts to determine the roles of individual viral genes in HSV-1 reactivation. For example, in the absence of the "nonessential" viral immediate-early protein, ICP0, HSV-1 is severely impaired in its ability to (i) replicate at the site of inoculation and (ii) establish latency in neurons of the peripheral nervous system. The mouse ocular model of HSV latency was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
57
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 55 publications
6
57
0
Order By: Relevance
“…2B). The reactivation efficiency of 7134 was about 10%, consistent with the previous studies of Cai et al (6) and Halford and Schaffer (22).…”
Section: Resultssupporting
confidence: 81%
“…2B). The reactivation efficiency of 7134 was about 10%, consistent with the previous studies of Cai et al (6) and Halford and Schaffer (22).…”
Section: Resultssupporting
confidence: 81%
“…9,34 This has always been attributed to its myelosuppressive effects without attempts to further define in more detail the molecular basis for this capacity. Interestingly, CPA has been associated with a decrease in iNOS production in alveolar macrophages in response to mycoplasma.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that a reduction in the size of the inoculum of ICP0-null mutants from 2 ϫ 10 6 to 2 ϫ 10 5 PFU/eye coupled with transient immunosuppression of mutant-infected mice can be used to enable HSV-1 ICP0-null mutant genomes to reach wild-type levels in the TG of latently infected mice (11). Utilizing this procedure to equalize mutant and wild-type genome loads, the goal of the present study was to determine if loss of ICP0 function impairs HSV-1 reactivation from latency.…”
mentioning
confidence: 99%